AN ENGLISH PROFICIENCY STUDY ON STUDENTS OF A DEVELOPING ISLAMIC HIGHER EDUCATION - ROFIK, ABDUR; CHRISTINA, CHRISTINA; HIDAYAH, ATINIA (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2020)
This is a case study that aims at analyzing students' English proficiency as reflected in students' TOEFL-Like scores at Universitas Sains Alqur'an Central Java in Wonosobo, Indonesia particularly years 2017, 2018, and 2019. The study focuses on students' achievement of English proficiency embedded in TOEFL-Like scores which consist of three sections, namely Listening, Structure and Written Expression, and comprehension of Reading. Considering the huge number of the data (2811 participants), to do the research, the data are conducted statistically using the SPSS application. In detail, the data were analyzed using descriptive statistics to find mean (to know students proficiency achievement), minimum, maximum and standard deviation values (to know the variance of students' English proficiency levels). Categorization of the proficiency levels is referred to Common European Framework of Reference for Languages (CEFR) standard. The study revealed that structure and written expression is the most difficult test faced then consecutively reading and listening. Then, the lowest and the highest scores were 217 and 567 with a standard deviation 31, 4. Furthermore, the mean of the total TOEFL-Like score achieved was 369, 09. Therefore, the students were mostly categorized as basic users (A2). The study suggests that an appropriate module can be considered to help the students to reach better proficiency, especially in a matter of structure and written expression section.